The killer book of serial killers: incredible stories, facts and trivia from the world of serial killers - Philbin, Tom (Sourcebooks, 2009)
Meet the serial killer -- Albert Fish -- Bobby Joe Long -- Ted Bundy -- Dean Corll -- Gary Heidnik -- John Wayne Gacy -- Albert Desalvo -- Jerry Brudos -- Henry Lee Lucas/Ottis Toole -- Jeffrey Dahmer -- David Berkowitz -- Ken Bianchi/Angelo Buono -- Dennis Rader -- Edmund Kemper -- Richard Ramirez -- Robert Hansen -- Harvey Glatman -- Ed Gein -- Wayne Williams -- Gary Ridgway -- Leonard Lake And Charles Ng -- Aileen Wuornos -- Marko Milat, Australia -- Paul Bernardo and Karla Homolka, Canada -- Pedro Lopez, Colombia -- Dennis Nilsen, England -- Henri Landru, France -- Peter Kurten, German -- Bela Kiss, Hungary -- Ahmad Suradgi, Indonesia -- Kodairo Yoshio, Japan -- Arnfinn Nesset, Norway -- Karl Denke, Poland -- Andrei Chikatilo, Russia -- Moses Sithole, South Africa -- Confessions